Early assisted discharge with generic community nursing for chronic obstructive pulmonary disease exacerbations: results of a randomised controlled trial. Issue 5 (16th October 2012) - Utens, Cecile M A; Goossens, Lucas M A; Smeenk, Frank W J M; Rutten-van Mölken, Maureen P M H; van Vliet, Monique; Braken, Maria W; van Eijsden, Loes M G A; van Schayck, Onno C P
Abstract : Objectives: To determine the effectiveness of early assisted discharge for chronic obstructive pulmonary disease (COPD) exacerbations, with home care provided by generic community nurses, compared with usual hospital care. Design: Prospective, randomised controlled and multicentre trial with 3-month follow-up. Setting: Five hospitals and three home care organisations in the Netherlands. Participants: Patients admitted to the hospital with an exacerbation of COPD. Patients with no or limited improvement of respiratory symptoms and patients with severe unstable comorbidities, social problems or those unable to visit the toilet independently were excluded. Intervention: Early discharge from hospital after 3 days inpatient treatment. Home visits by generic community nurses. Primary outcome measure was change in health status measured by the Clinical COPD Questionnaire (CCQ). Treatment failures, readmissions, mortality and change in generic health-related quality of life (HRQL) were secondary outcome measures. Results: 139 patients were randomised. No difference between groups was found in change in CCQ score at day 7 (difference in mean change 0.29 (95% CI −0.03 to 0.61)) or at 3 months (difference in mean change 0.04 (95% CI –0.40 to 0.49)). No difference was found in secondary outcomes. At day 7 there was a significant difference in change in generic HRQL, favouring usual hospital care. Conclusions: While patients' disease-specific health status after 7-day treatment tended to be somewhat better in the usual hospital care group, the difference was small and not clinically relevant or statistically significant. After 3 months, the difference had disappeared. A significant difference in generic HRQL at the end of the treatment had disappeared after 3 months and there was no difference in treatment failures, readmissions or mortality. Early assisted discharge with community nursing is feasible and an alternative to usual hospital care for selected patients with an acute COPD exacerbation. Trial registration: NetherlandsTrialRegister NTR 1129.